Redox species and oxygen fugacity of slab-derived fluids: Implications for mantle oxidation and deep carbon-sulfur cycling - Li, Yi-Bing; Chen, Yi; Su, Bin; Zhang, Qing-Hua; Shi, Kai-Hui (Frontiers in Earth Science, 2022)
The generation and migration of slab-derived fluids are essential for understanding subduction zone seismicity, arc magmatism, and deep volatile cycle. However, the redox species and oxygen fugacity (fO2) of slab-derived fluids are highly debated. Here we conduct phase equilibria modeling with altered oceanic crust (AOC) and serpentinites along typical subduction geotherms in the C-S-bearing system. Based on the averaged compositions of AOC and serpentinite, our calculated results show that oxidized carbon-sulfur species dominate slab-derived fluids during slab subduction. As a result, the fO2 of slab-derived fluids increases with subduction depth. The predicted species is compatible with fluid inclusions observed from oceanic HP metamorphic rocks. In addition, the oxidation state of slab-derived fluids is primarily controlled by the redox budget (RB) of the slab prior to subduction. Subduction zone thermal structure, however, does not significantly influence the slab fluid fO2, which is supported by the similar fO2 ranges in arc lavas from cold and hot subduction zones. Our models in the open system further show that most of carbon (>70%) and sulfur (>50%) in the cold subducted slab would be lost at subarc depths, suggesting the arc system as a key region for C-S output. Small amounts of carbon and sulfur could be transported into the deeper mantle via the closed-system subduction and open-system cold subduction, supplying the source materials for volatile-rich intraplate magmas and superdeep diamonds.